B lymphocytes inactivation by Ibrutinib limits endometriosis progression in mice. Issue 7 (27th June 2019) - Riccio, L G C; Jeljeli, M; Santulli, P; Chouzenoux, S; Doridot, L; Nicco, C; Reis, F M; Abrão, M S; Chapron, C; Batteux, F
Abstract: STUDY QUESTION: What are the effects of B lymphocyte inactivation or depletion on the progression of endometriosis? SUMMARY ANSWER: Skewing activated B cells toward regulatory B cells (Bregs) by Bruton's tyrosine kinase (Btk) inhibition using Ibrutinib prevents endometriosis progression in mice while B cell depletion using an anti-CD20 antibody has no effect. WHAT IS KNOWN ALREADY: A polyclonal activation of B cells and the presence of anti-endometrial autoantibodies have been described in a large proportion of women with endometriosis though their exact role in the disease mechanisms remains unclear. STUDY DESIGN, SIZE, DURATION: This study included comparison of endometriosis progression for 21 days in control mice versus animals treated with the anti-CD20 depleting antibody or with the Btk inhibitor Ibrutinib that prevents B cell activation. PARTICIPANTS/MATERIALS, SETTING, METHODS: After syngeneic endometrial transplantation, murine endometriotic lesions were compared between treated and control mice using volume, weight, ultrasonography, histology and target genes expression in lesions. Phenotyping of activated and regulatory B cells, T lymphocytes and macrophages was performed by flow cytometry on isolated spleen and peritoneal cells. Cytokines were assayed by ELISA. MAIN RESULTS AND THE ROLE OF CHANCE: Btk inhibitor Ibrutinib prevented lesion growth, reduced mRNA expression of cyclooxygenase-2, alpha smooth muscle actin and type I collagen in the lesions and skewed activated B cells toward Bregs in the spleen and peritoneal cavity of mice with endometriosis. In addition, the number of M2 macrophages decreased in the peritoneal cavity of Ibrutinib-treated mice compared to anti-CD20 and control mice. Depletion of B cells using an anti-CD20 antibody had no effect on activity and growth of endometriotic lesions and neither on the macrophages, compared to control mice. LARGE SCALE DATA: N/A. LIMITATIONS, REASONS FOR CAUTION: It is still unclear whether B cell depletion by the anti-CD20 or inactivation by Ibrutinib can prevent establishment and/or progression of endometriosis in humans. WIDER IMPLICATIONS OF THE FINDINGS: Further investigation may contribute to clarifying the role of B cell subsets in human endometriosis. STUDY FUNDING/COMPETING INTEREST(S): This research was supported by a grant of Institut National de la Santé et de la Recherche Médicale and Paris Descartes University. None of the authors has any conflict of interest to disclose.